The Development of Early Literacy Skills Indicators (ELSI) for Children Aged 3+ to 4+ Years - Bacotang, Juppri; Mohamed Isa, Zainiah; Che Mustafa, Mazlina; Farhana Md. Yasin, Siti (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to develop an Early Literacy Skills Indicators (ELSI) to assess early literacy skills, which includes five components, namely language and communication, concept of print and environmental print, phonemic and phonetic, reading and narrative comprehension, and early writing for children aged 3+ to 4+ years. The development of ELSI design was based on the ADDIE-ELSI Model, which consists of five stages: analysis, design, development, implementation, and evaluation. The researchers analyzed documents and involved three experts, 43 educators, and 40 children aged 3+ to 4+ years as respondents for data collection. This study succeeded in developing ELSI with emphasis on principles such as authentic, balanced, and integrated; standardized; individual; and interactive. ELSI has good content validity, difficulty index, and discrimination index in assessing children’s early literacy skills. In conclusion, ELSI was developed systematically and empirically and could accurately assess early literacy skills of children aged 3+ to 4+ years.